(untitled) - King, Laura A. (New York, 2012)
Each chapter is broken down into 2-4 smaller modules, allowing instructors to assign the content they want, in the order they prefer. With Connect Psychology, instructors can customize content and course materials to meet the needs of their course. Real-time reports show how well each student is performing on each course segment. Real time reports show how well each student is performing on each course assignment. Instructors can use this feature to spot problem areas before they crop up on an exam.
Keywords: Psychology,Tâm lý học; Study and teaching,Dạy và học